The agile mind - Koutstaal, Wilma (New York : Oxford University Press, 2012)
In this book, Wilma Koutstaal covers all aspects of agile thought, and how it emerges from and interacts with memory perception, emotion, executive control, motivation, and action as well as how it is related to creativity, mediated by learning and environmental input, enhanced by plasticity, and destroyed by rigidity.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 20, 2012).
Includes bibliographical references and index.
Keywords: Thought and thinking; Creative thinking; Divergent thinking; Adaptability (Psychology)